2014
DOI: 10.14740/jcs244e
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Challenge of Acute Appendicitis: Appraisal Through Alvarado Score

Abstract: Background: Acute appendicitis is a common surgical emergency which, even with modern diagnostic facilities, remains a challenging task for the surgeon. The variations in presentation pertaining to time, signs and symptoms can baffle even the very experienced surgeons. The aim of the study was to find out the predictive value of the Alvarado scoring system in diagnosis of acute appendicitis and its clinical applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to Chandio, et al [32] the Alvarado score was found accurate with a p-value of 0.0001 depending on the score points as follows.…”
Section: Interpretation Of the Improved Alvarado Score (Mantrels)mentioning
confidence: 99%
“…According to Chandio, et al [32] the Alvarado score was found accurate with a p-value of 0.0001 depending on the score points as follows.…”
Section: Interpretation Of the Improved Alvarado Score (Mantrels)mentioning
confidence: 99%
“…According to Chandio, et al [32] the Alvarado score was found accurate with a p-value of 0.0001 depending on the score points as follows. In the majority of the studies, a score of 1-4 ruleout the diagnosis of acute appendicitis, and a score of 7 or more confirms the diagnosis.…”
Section: Interpretation Of the Improved Alvarado Score (Mantrels)mentioning
confidence: 99%